Muslim Consumer Behavior in Consuming Halal Food in Muslim Minority Communities - Hidayati, Amalia Nuril; Suman, Agus; Noor, Iswan; Badriyah, Nurul (Journal of Ecohumanism, 2024)
Consumption is an important factor that drives production and distribution activities. Halal food consumption is increasingly becoming a concern, especially in non-Muslim majority countries. As Indonesia’s leading tourism destination, Bali has great potential to contribute to economic growth through MSMEs. Halal food consumption preferences are easier to find in Muslim-majority areas but have become an interesting issue in areas with Muslim minorities, especially in understanding halal consumption choices in these communities. This reflects challenges in the distribution and accessibility of halal products in some areas. This study aims to analyze Muslim consumer preferences for halal food consumption in minority Muslim communities in Bali Province. This research uses an associative quantitative approach. Data were obtained from primary data and secondary data. The sample analyzed was 390 using a questionnaire. The tests carried out include the data stationarity test, lag optimum, model stability, Granger causality, and cointegration. The results showed that: 1) Price is not a significant factor for Muslim consumers in minority communities; halal and spiritual beliefs are prioritized. 2) Taste is an essential factor, where consumers choose halal food that suits local flavors and culture. 3) Trust in halal labeling is crucial, especially in areas with limited information on halal products. 4) Religiosity remains a key driver in halal food consumption, with high levels of religiosity in minority communities in Bali. 5) Subjective norms significantly influence Muslim consumer preferences in consuming halal food 6) Limited accessibility of halal food forces consumers to rely on local communities and halal labels. Based on the results of the analysis conducted, it can be concluded that although Balinese society is generally not dominated by Muslim consumers, these factors remain relevant for the halal food market in Bali, especially for Muslim tourists or local Muslim consumers who are looking for products that are by their beliefs.